Pyrolytic wood vinegar from industrial crop residues as a bio-based fungicide for Fusarium control in banana cultivation - Purnama, Indra; Saidi, Noor Baity; Mutamima, Anisa; Baharum, Nadiya Akmal; Anggrayni, Dilla; Boukherroub, Rabah; Abderrahmani, Amar; Novianti, Fawzia; Wijaya, Karna; Apriyanto, Mulono; Saviola, Aldino Javier; Aziz, Muhammad (Elsevier B.V., 2026)
The thermochemical valorization of industrial crop residues into bio-based inputs offers a sustainable pathway for waste utilization and crop protection. In this study, we evaluated the antifungal efficacy of wood vinegar (pyroligneous acid) produced via slow pyrolysis at 210 °C from four lignocellulosic feedstocks—coconut shell (Cocos nucifera), palm kernel shell (Elaeis guineensis), acacia wood (Acacia mangium), and mahang wood (Macaranga gigantea)—against Fusarium oxysporum f. sp. cubense Tropical Race 4 (Foc TR4), the causal agent of Fusarium wilt in banana. Gas chromatography–mass spectrometry (GC–MS) revealed that palm kernel shell and coconut shell vinegars contained high levels of acetic acid, phenol, and furfural. In vitro assays, supported by standardized turbidity scoring, showed complete inhibition at 0.8 % (palm kernel) and 1.2 % (coconut shell), with fungicidal activity confirmed by the absence of regrowth on agar media. Greenhouse trials with 2 % soil drench applications over 11 weeks significantly suppressed wilt, reducing the Disease Severity Index (DSI) to 4–8 % compared with 54 % in the inoculated control. Coconut shell vinegar further enhanced plant performance, producing the highest gains in height (+22.1 cm), leaf emergence (+2.9), and pseudostem diameter (+0.90 cm). The innovative contribution of this study lies in demonstrating, for the first time, that underutilized tropical residues can yield low-toxicity fungicides effective at < 2 % concentrations, supported by integrated chemical, in vitro, and in vivo evidence. These findings underscore the potential of wood vinegar as a scalable, eco-friendly biopesticide while advancing circular bioeconomy strategies for tropical agriculture.